2022
DOI: 10.3390/f13040505
|View full text |Cite
|
Sign up to set email alerts
|

Rewetting Tropical Peatlands Reduced Net Greenhouse Gas Emissions in Riau Province, Indonesia

Abstract: Draining deforested tropical peat swamp forests (PSFs) converts greenhouse gas (GHG) sinks to sources and increases the likelihood of fire hazards. Rewetting deforested and drained PSFs before revegetation is expected to reverse this outcome. This study aims to quantify the GHG emissions of deforested PSFs that have been (a) reforested, (b) converted into oil palm, or (c) replanted with rubber. Before rewetting, heterotrophic soil respiration in reforested, oil palm, and rubber plantation areas were 48.91 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Greater emission reductions can be achieved when the water table is kept closer to the surface (Karki et al 2014) but any reduction in drainage depth likely results in some level of emission reductions. For example, Lestari et al (2022) report a 17-18% reduction in soil GHG emissions from oil palm and rubber plantations (Table 2) following rewetting despite the water table remaining 40-100 cm below the surface. Evans et al (2021) observed a strong linear relationship between peatland CO2 emissions and water table across a range of undisturbed and drained peatlands.…”
Section: Mitigating Ghg Emissions Associated With Peatland Disturbancementioning
confidence: 99%
“…Greater emission reductions can be achieved when the water table is kept closer to the surface (Karki et al 2014) but any reduction in drainage depth likely results in some level of emission reductions. For example, Lestari et al (2022) report a 17-18% reduction in soil GHG emissions from oil palm and rubber plantations (Table 2) following rewetting despite the water table remaining 40-100 cm below the surface. Evans et al (2021) observed a strong linear relationship between peatland CO2 emissions and water table across a range of undisturbed and drained peatlands.…”
Section: Mitigating Ghg Emissions Associated With Peatland Disturbancementioning
confidence: 99%
“…Peatland rewetting is an alternative to the conversion of peatland to cultivated land. Many studies have confirmed rewetting's positive impact on water levels and that it positively affects microbial peat oxidation (Jauhiainen et al, 2013;Könönen et al, 2018;Lestari et al, 2022). Peatland rewetting can eliminate drainage in an area and increase the ecosystem's capacity to maintain the water level during the dry season; hence, reducing the area's vulnerability to fire (Lestari et al, 2022;Ritzema et al, 2014;Taufik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In forested peatland, the chamber method cannot capture CO 2 fluxes from tree respiration but may capture CO 2 fluxes from roots and understorey vegetation respiration; therefore, reporting the CO 2 fluxes as soil respiration is preferable. For example, Jauhainen et al ( 2008) and Lestari et al (2022) reported carbon fluxes in tropical forested peatlands in the form of soil respiration (SRt). Meanwhile, many of their counterpart from temperate and boreal zones reported carbon fluxes in the form of ecosystem respiration (Haddaway et al 2014).…”
Section: Introductionmentioning
confidence: 99%